Realización de un cortometraje documental que visibilice como el plástico es amenaza para las especies marinas y terrestres en el puerto de la Isla Santa Cruz/Galápagos - Yucailla Toabanda, Erick Geovanni (2020)
This project is a documentary short film, it demonstrates and exhibits how plastic affects the ecosystems, flora, and fauna. It also affects the land based and marine territory of Santa Cruz Island Port in the Province of Galapagos. Additionally, set the measures that are taking into account to solve these problems…